2012
DOI: 10.1097/pcc.0b013e318238b272
|View full text |Cite
|
Sign up to set email alerts
|

Personnel and unit factors impacting outcome after cardiac arrest in a dedicated pediatric cardiac intensive care unit*

Abstract: Our data suggest that personnel and unit factors may impact outcome after cardiac arrest in a pediatric cardiac intensive care unit. Weekend arrests and less experience of the primary nurse were risk factors for unsuccessful resuscitation. Neither presence at arrest onset nor experience of the attending cardiac intensivist was associated with outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 21 publications
2
33
1
1
Order By: Relevance
“…They defined a "failure to rescue" rate as the ability to prevent a clinically important deterioration (ie, death or permanent disability) from a complication. 16 Review of cardiac surgical data at our institution demonstrates that our overall incidence of cardiopulmonary arrests is similar to the incidences reported in other published data series 3,4,17 at 3% to 6% per year. The Get With The Guidelines-Resuscitation database www.ajcconline.org report 13 from 2011 reported a subgroup of cardiac surgical patients with a survival to discharge of 37%, which was similar to our experience in 2010 and 2011.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…They defined a "failure to rescue" rate as the ability to prevent a clinically important deterioration (ie, death or permanent disability) from a complication. 16 Review of cardiac surgical data at our institution demonstrates that our overall incidence of cardiopulmonary arrests is similar to the incidences reported in other published data series 3,4,17 at 3% to 6% per year. The Get With The Guidelines-Resuscitation database www.ajcconline.org report 13 from 2011 reported a subgroup of cardiac surgical patients with a survival to discharge of 37%, which was similar to our experience in 2010 and 2011.…”
Section: Discussionsupporting
confidence: 66%
“…Over time, our survival rate after cardiopulmonary arrest has improved each year with survival to discharge reaching 55% in 2012 and 81% in 2013, exceeding reported survival rates of 37% to 48% in this specific population. 13,17 This survival rate would suggest that our heart center has lowered our failure-to-rescue rate specifically related to cardiopulmonary arrests in the cardiac surgical patients. Additionally, we have noticed a downward trend, which is not yet significant, in the percentage of cardiopulmonary arrests deemed "potentially preventable."…”
Section: Discussionmentioning
confidence: 99%
“…This result is different from a recent study [8] which reported that less experience of the primary nurse caring for a patient, and weekend timing of an arrest event may increase the likelihood of failure to resuscitate cardiac arrest in a dedicated pediatric cardiac ICU [8]. Other reports also suggest that nurses are greater experience are more likely to provide rapid diagnosis of cardiac arrest and pre-arrest intervention to prevent arrest in pediatric patients [11][12][13][14].…”
Section: Discussionmentioning
confidence: 61%
“…Investigations focused on system factors of pediatric cardiac arrest are scarce [8][9][10]. We assessed the impact of system factors (timing and date of cardiac arrest, nursing experience, staffing of the unit) and modifiable intensive care unit (ICU) interventions (sedation, analgesia, central venous access) on outcome from cardiac arrest in a Pediatric intensive care unit.…”
mentioning
confidence: 99%
“…But it has also been shown that the outcome of cardiac arrest at the PICU, independent of the underlying cause of cardiac arrest, relies on many other variables. Among these are experience of nursing staff, arrest procedures at weekends, and PICU unit-specific factors (4). As a cardiac arrest procedure is mainly a team effort, the quality of the CPR *See also p. 1688. team performance might also be an important factor.…”
mentioning
confidence: 99%